Pengaruh Komponen Risk-Based Bank Rating Terhadap Profitabilitas Bank Umum Syariah Di Indonesia (Periode 2011–2014) - Bunga Aprigati Iskandar; Nisful Laila (Universitas Airlangga, 2016)
This research aimed to know and analyze the influence of components of Risk based bank rating method (risk profile, Good Corporate Governance, earnings, and capital) to profitability of Islamic Bank in Indonesia, measured by Return On Assets (ROA). Whereas the ratio used in this research to represent the components of RGEC are risk profile measured by Non Performing Financing (NPF) and Financing to Deposit Ratio (FDR), implementation of GCG by composite score of GCG, earnings by Operational Efficiency Ratio (OER), and capital by Capital Adequacy Ratio (CAR). Sample of this research are 11 Islamic Banks in Indonesia from 2011 to 2014. The analysis techniques used is multiple linear regression. Based on the analysis result, it can be concluded that NPF, FDR, GCG, OER, and CAR had simultaneous significant effect to ROA. Partially, NPF, FDR, and BOPO have significant effect to ROA. However, CAR and GCG don’t affect ROA significantly.